Near-surface crystallization of PET - Shinotsuka, K; Bliznyuk, V; Assender, H (Elsevier, 2012)
The near-surface crystallization behaviour of poly(ethylene terephthalate) films of various thickness, spin-cast from solution onto silicon substrates, has been studied. In the as-cast state, the films are amorphous, with featureless morphology. A relationship is mapped between the film thickness (in the range 3 nm-700 nm), the isothermal annealing temperature (ambient to 150°C), and the crystalline morphology. Two distinct morphologies are observed which are associated with surface-specific crystallization and bulk crystallization (producing much rougher film surfaces). The surface crystallization process is associated with a top-surface region (measured to be of about 13 nm in depth) of lower glass transition temperature, where, at temperatures between the surface and bulk crystallization temperatures, only the material in the more-mobile surface region is able to reorganize to form crystals. This phenomenon is observed for films of all the thicknesses studied and it is therefore concluded that this is not specifically a thin-film phenomenon, rather a surface-specific phenomenon possible in material of any thickness. © 2012 Elsevier Ltd. All rights reserved.